2015
DOI: 10.1371/journal.pone.0134590
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Liver in Determining Serum Colon-Derived Uremic Solutes

Abstract: Evidence has shown that indoxyl sulfate (IS) and p-cresyl sulfate (PCS) may be alternative predictors of clinical outcomes in chronic kidney disease (CKD). Both toxins are derived from the gastrointestinal tract and metabolised in the liver. However, it is unclear whether the liver affects the production of IS and PCS. Here, we explore the association between IS and PCS levels in liver cirrhosis and a CKD-based cohort (N = 115). Liver and kidney function was assessed and classified by a Child-Pugh score (child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 34 publications
(37 reference statements)
1
27
0
Order By: Relevance
“…Our results also revealed that IS was strongly negatively correlated with FMD and pulse wave velocity after adjusting for other confounding factors in a CKD cohort. This finding was concordant with a previous study showing that IS levels were directly correlated with aortic calcification and pulse wave velocity [5]. Additionally, IS was associated with atherosclerotic factor [28,29] and was a valuable surrogate marker in predicting cardiovascular disease in pre-dialysis patients [5,15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results also revealed that IS was strongly negatively correlated with FMD and pulse wave velocity after adjusting for other confounding factors in a CKD cohort. This finding was concordant with a previous study showing that IS levels were directly correlated with aortic calcification and pulse wave velocity [5]. Additionally, IS was associated with atherosclerotic factor [28,29] and was a valuable surrogate marker in predicting cardiovascular disease in pre-dialysis patients [5,15].…”
Section: Discussionsupporting
confidence: 92%
“…Previous in vitro studies showed that IS had a specific toxic effect on vascular endothelial cells [8], smooth muscle cells [9], and renal tubular cells [10,11]. Clinical outcome studies also demonstrated that IS may play a major role in cardiovascular and all-cause mortality in CKD patients, including those on hemodialysis [5,[12][13][14][15]. These adverse effects may be directly or indirectly attributed to endothelial dysfunction as a result of exposure to retained uremic toxins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He found that the dogs with surgically-removed digestive tracts given indole still had elevated indoxyl sulfate plasma levels, whereas dogs with hepatectomies did not. A more recent study by Lin et al [26] confirms the role of the liver in indoxyl sulfate production. They found that cirrhosis limited the increase in plasma indoxyl sulfate levels in patients with CKD.…”
Section: Characteristicsmentioning
confidence: 82%
“…The biotransformation of indoxyl sulfate requires CYP2E1 and SULT1A1 hepatic enzymes and demonstrates the importance of these pathways in microbiota-derived uremic toxin formation (Figure 2). Formation of p-cresol sulfate and indoxyl sulfate is decreased in chronic kidney disease patients and animal models with advanced liver cirrhosis (and thus impaired hepatic metabolism) [28]. Cirrhotic patients also exhibit higher serum concentrations of metabolic precursors like phenol and indole, suggesting decreased metabolic conjugation [29,30].…”
Section: Intestinal Microbiota-host Liver Interactionsmentioning
confidence: 99%